Comparison of the Effects of Static-Stretching and Tubing Exercises on Acute Shoulder Range of Motion in Collegiate Baseball Players - Andrew M Busch; Jackson Browstein; Richard Ulm (International Journal of Sports Physical Therapy)
# Background The overhead throwing motion repetitively stresses the dominant arm in baseball players, frequently altering normal range of motion (ROM) in multiple directions. Baseball players regularly perform a combination of static stretches (SS) and dynamic tubing (DT) resistance exercises in pre-throwing warm-up routines intended to improve shoulder ROM and reduce injuries.